Effective topical treatments using innovative NNO-tridentate vanadium(iv) complexes-mediated photodynamic therapy in a psoriasis-like mouse model. Issue 25 (7th June 2022) - Lin, Rong-Kai; Venkatesan, Parthiban; Yeh, Chao-Hsuan; Chien, Ching-Ming; Lin, Te-Shan; Lin, Chi-Chen; Lin, Chu-Chieh; Lai, Ping-Shan
Abstract : In a psoriasis-like mice model, NNO-tridentate vanadium(iv ) complexes were synthesized for photodynamic therapy. Abstract : Psoriasis is a chronic inflammatory skin disease that can significantly impact the quality of human life. Various drug treatments are available; however, due to their long-term severe side effects the usage of these drugs is limited. Photodynamic therapy (PDT) has been clinically approved for skin diseases due to its non-invasive nature. We present novel NNO-tridentate vanadium(iv ) complexes used in PDT for anti-inflammatory effects in an imiquimod-induced psoriasis-like skin disease mouse model. The vanadium(iv ) complexes (1–4 ) were synthesized using the NNO-tridentate ligand with a benzo[ i ]dipyrido[3, 2- a ;2′, 3′- c ]phenazine (dppn) moiety, and were characterized by UV/Visible spectroscopy, EPR spectroscopy, NMR ( 1 H, and 13 C) spectroscopy, electrospray ionization mass (ESI-MS) spectrometry and cyclic voltammetry (CV) studies. The photocytotoxicity of vanadium(iv ) complexes (1–4 ) was low under dark conditions and complex (4 ) showed remarkable photocytotoxicity under blue light (430 nm, 8 W cm −2, 30 min) irradiation. Moreover, [VO( t -butylL)(dppn)] (4 )-mediated PDT down-regulated inflammatory cytokines IL-17A and IL-22 in the psoriasis-like mouse model, which could evidence the significant relieving of the psoriatic-like symptoms in the mouse model. Overall, these results suggested that [VO( t -butylL)(dppn)] (4 ) could be a potential candidate for the treatment of psoriasis both in vitro and in vivo .